Investigation of forming accuracy in mandrel-free hot-spinning. (2017) - Imamura, Yoshihide; Ikawa, Ken; Sakane, Yuto; Iwasaki, Hayato; Hirakawa, Takeo
Abstract: A new mandrel-free hot-spinning was developed as a new near-net-shape forming technology. Hot-spinning provides a high flexibility, because of no mandrel. This paper investigated the material properties and dimensional accuracy of mandrel-free hot-spun Ti-6Al-4V alloy conical product with a wall angle of 30°at 900°C. It was found that the deformation in the process roughly followed the sine law. It is confirmed that shape control is possible by adjusting the roller path. Product thickness tended to be thicker than the thickness predicted by the sine law and the flange part is tilted in the direction of forming progress when the initial thickness was large. It is presumed that a certain amount of bending deformation takes place in the process and strain distribution in the thickness direction was caused during forming. For the purpose of improving forming accuracy in the mandrel-free hot-spinning, reducing the strain distribution in the thickness direction, including optimization of the temperature distribution in the thickness, and optimization of the roller feed ratio, may be most effective factors.